Klausula Baku Pada Perjanjian Berjangka Dan Perlindungan Hukum Bagi Investor Perdagangan Berjangka Komoditi - Namira, Sheila (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2022)
Legal protection of customers or investors in the world of commodity futures trading needs to be considered. Many victims of the case of